INTERNET- mreža među prednosti i slabosti - Blaževska, Daniela (In Medias Res, Centar za filozofiju medija i mediološka istraživanja, 2022)
Sažetak Internet je „međunarodni sistem kompjutera koji vam omogućava da vidite informacije iz cijeloga svijeta na vašem kompjuteru i da pošaljete informacije drugim kompjuterima” (Oxford English-Serbian Student’s Dictionary, 2006:447). Cilj ovog rada je istražiti prednosti i slabosti interneta. Internet je mreža između slobode i zloupotrebe, prava i zakona, znanja i ograničenja. Internet je među granicama. Abstract The Internet is the „international system of computers that makes it possible for you to see information from all around the world on your computer and to send information to other computers” (Oxford English- Serbian Student’s Dictionary, 2006: 447) The aim of this paper is to research the advantages and weaknesses of the Internet. Internet- network between freedom and misuse, right and law, knowledge and limit. Internet between borders.
Keywords: Ključne riječi: internet, informacije, mreža, kompjuter, prednosti i slabosti interneta. Key words: internet, information, network, computer, advantages and weaknesses of the internet.